Ted Williams [videorecording (DVD)] - Davis, Nick, 1965-; Hamm, Jon, 1971- (American masters, 2018)
A complex and entertaining portrait of Ted Williams who was as obsessive as he was talented, the documentary reveals his complicated relationships with family and friends and explores the impact he has had on the current generation of MLB stars. Features Bob Costas, Wade Boggs, Roger Angell and Joey Votto. Narrated by Jon Hamm.